Perancangan Website Penjualan Dan Promosi Pada Sentra Kerajinan Rotan Asmidar Padang - Romi Wijaya; Masriadi Masriadi; Muhammad Ikhlas (Journal Information System Development (ISD), 2020)
Abstract-- Internet technology has proven to be one of the effective and efficient information media in the dissemination of information that can be accessed by anyone, anytime and anywhere. The rapid development of web applications since the advent of internet technology has greatly helped in the ease and speed of sending, delivering and receiving information. During this time, Sentra Kerajinan Rotan Asmidar Padang which is engaged in selling various kinds of rattan handicrafts such as swings, sand baskets, parcel, motorcycle baskets, rattan chairs, bags and many other handicrafts, promotions are still using paper facilities, brochures, and other similar facilities. These constraints make product promotion less effective, besides, customers who want to see product information available at the Sentra Kerajinan Rotan Asmidar Padang need to visit the store. Therefore, the authors and researchers are interested in designing a web application for sales and promotion. So that it can fulfill customers’ need of information that they want. It will also safe their time with the efficient system. The information system created is expected to run well, as well as providing solutions to the lack of time efficiency in sales and promotion.Keywords: Website, Information, Sales, Promotion